Male and Female Voices in Economics - Hans Henrik Sievertsen; Sarah Smith (Institute of Labor Economics (IZA), 2022)
Women's voices are likely to be even more absent from economic debates than headline figures on female under-representation suggest. Focusing on a panel of leading economists we find that men are more willing than women to express an opinion and are more certain and more confident in their opinions, including in areas where both are experts. Women make up 21 per cent of the panel but 19 per cent of the opinions expressed and 14 per cent of strong opinions. We discuss implications for the economics profession and for promoting a genuine diversity of views.
Keywords: A11; J16; 330; gender; economics profession